Handbook of Group Decision and Negotiation - Kilgour, D. Marc.; Eden, Colin; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2010)
The growing field of Group Decision and Negotiation is best described as the empirical, formal, computational, and strategic analysis of group decision-making and negotiation, especially from the viewpoints of Management Science and Operations Research. The topic crosses many traditional disciplinary boundaries. It has connections to business administration and business strategy, management science, systems engineering, computer science, mathematics, and law, as well as economics, psychology, and other social sciences. This defining handbook provides an up-to-date reference on new approaches to the principles and practice of negotiation, group decision-making, and collaboration, including the origins, development, and prospects of electronic negotiation, as well as the associated development of on-line or computer-based arbitration systems. It also provides a current and comprehensive reference on how traditional issues in negotiation, such as knowledge, language, strategy, fairness and justice, have been transformed by technology. Until now, this advancing field has lacked a comprehensive, accurate, reliable, and readable reference. This handbook satisfies this need, and is set to become the major reference in the field.
The Context of Group Decision and Negotiation -- to the Handbook of Group Decision and Negotiation -- Group Decisions and Negotiations in the Knowledge Civilization Era -- (3z(BInvisible Whispering(3y(B: Restructuring Meeting Processes with Instant Messaging -- Soft Computing for Groups Making Hard Decisions -- Emotion in Negotiation -- Doing Right: Connectedness Problem Solving and Negotiation -- The Role of Justice in Negotiation -- Analysis of Negotiation Processes -- Analysis of Collective Decisions: Principles and Procedures -- Non-Cooperative Bargaining Theory -- Cooperative Game Theory Approaches to Negotiation -- Voting Systems for Social Choice -- Fair Division -- Conflict Analysis Methods: The Graph Model for Conflict Resolution -- The Role of Drama Theory in Negotiation -- Facilitated Group Decision and Negotiation -- Group Support Systems: Overview and Guided Tour -- Multicriteria Decision Analysis in Group Decision Processes -- The Role of Group Decision Support Systems: Negotiating Safe Energy -- The Effect Of Structure On Convergence Activities Using Group Support Systems -- Systems Thinking, Mapping, and Modeling in Group Decision and Negotiation -- Facilitated Group Decision Making in Hierarchical Contexts -- Collaboration Engineering -- Electronic Negotiation -- Electronic Negotiations: Foundations, Systems, and Processes -- The Adoption and Use of Negotiation Systems -- Support of Complex Electronic Negotiations -- Online Dispute Resolution Services: Justice, Concepts and Challenges -- Agent Reasoning in Negotiation.s
Keywords: Economics; Artificial intelligence; Mathematics; Economics, Mathematical; Operations research; Economics/Management Science; Operation Research/Decision Theory; Game Theory, Economics, Social and Behav. Sciences; Artificial Intelligence (incl. Robotics).; Game Theory/Mathematical Methods